Schematic Structure and Stance in Students’ Writing in Business Communication: A Comparative Study of Native English Speaking and Iranian Students - Arezou Bakhtiari (Journal of Language and Literature, 2021)
This study reports on two knowledge elements of stance and schematic structure in order to help novice students increase the efficacy of their writing in business communication. With this regard, Santos’ (2002) Business Letters of Negotiation Model and Hyland’s (2005b) Stance Model of Interaction were drawn upon. Sixty business emails written by native English speaking (NS) and Iranian students of Business Management Departments in universities were analyzed. Two raters explored the corpus for their moves/steps frequencies and a concordance software was used in order to explore stance markers frequencies. To investigate whether Iranian and NS writers are statistically different from each other, the findings of frequencies were submitted to one-variable Chi-square test. The results showed that NS and Iranian writers are not different from each other in their content staging while they are providing information/answers or negotiating. Running counter to moves 2 and 23, move 3 turned out to have different results; there was a significant difference between NS and Iranian writers in their request of information/action/favors. Results presented no significant difference between NS and Iranian writers in their employment of hedges and attitude markers of stance with regard to one-variable Chi-square test results. For boosters, Chi-square test detected a significant difference between the groups only in move 2. There was a significant difference, however, between NS and Iranian writers in their use of self-mention markers in moves 3 and 23. The results of this paper have both theoretical and pedagogical significance.